Detection of Chlamydia trachomatis in an Australian high school student population. Issue 3 (1st June 2002) - Debattista, J; Martin, P; Jamieson, J; Crane, K; Dolton, I; Russell-Hall, S; DeSilva, J; Hargrave, R; Robinson, T; Ryan, N; Mortlock, M
Abstract : Objective: To assess the prevalence of Chlamydia trachomatis infections among an Australian high school adolescent population. Methods: Over a 4 year period, 14 high schools were selected in which an infertility prevention programme targeting C trachomatis was delivered to senior student populations. Coded first catch urine specimens were analysed by Amplicor PCR and infected students treated. Data retrospectively obtained from chlamydia screening programmes conducted among disadvantaged young people detached from formal education were also collated for comparison. Results: Of a total student test population of 1174, 15 (1.3%; 95% CI 0.7% to 2.1%) were diagnosed with C trachomatis. Of 516 females and 658 males, 12 (2.3%; 95% CI 1.1% to 4.1%) and 3 (0.5%; 95% CI 0.1% to 1.4%) were tested positive respectively. Data collated for three populations of disadvantaged youth returned at total of 89 C trachomatis infections out of 560 people (15.9% 95%CI 13.0–19.2%). Conclusion: The overall prevalence of C trachomatis infection among this population of senior high school adolescents is low, and significantly differs from the higher chlamydia rates detected in disadvantaged adolescents detached from formal schooling (p<0.0001).